Synthetic blends of volatile, phytopathogen-induced odorants can be used to manipulate vector behavior - Aksenov, Alexander A.; Martini, Xavier; Zhao, Weixiang; Stelinski, Lukasz L.; Davis, Cristina E. (Frontiers in Ecology and Evolution, 2014)
Volatile organic compounds (VOCs) are emitted from all plants and these VOCs are important means of communication between plants and insects. It has been documented that pathogen infections alter VOC profiles rendering infected plants more attractive to specific vectors transmitting these pathogens than uninfected plants, thus potentially aiding in pathogen propagation. Mimicking these chemical cues might enable insect attraction away from the plant or disruption of host finding behavior of the vector. However, the practical implications have not been fully explored. We used citrus, Diaphorina citri and huanglongbing (HLB) as a model host-vector-disease system because HLB threatens citrus production worldwide and is similar to other critical diseases of food crops, such as Zebra Chip affecting potato. We formulated a synthetic chemical blend using selected HLB-specific biomarker compounds, and tested the blend with the Attenu assay system for chemosensory proteins. The Attenu assay system is a procedure that identifies interactions between insect chemosensory proteins and their ligands. We found that an equimolar mixture of compounds mimicking the volatile profile of HLB-infected citrus bound chemosensory proteins. Further investigation of this blend in laboratory behavioral assays resulted in development of a synthetic lure that was more attractive to D. citri than natural citrus tree volatiles. This strategy could provide a new route to produce chemical lures for vector population control for a variety of plant and/or animal systems and it may result in the development of a practical lure for monitoring vectors of disease, such as D. citri.